Complexities of HIV Disclosure in Patients Newly Entering HIV Care: A Qualitative Analysis. (March 2020) - Chapman Lambert, Crystal; Tarver, Will L.; Musoke, Pamela L.; Stringer, Kristi L.; Whitfield, Samantha; Turan, Bulent; Modi, Riddhi; Mugavero, Michael J.; Fredericksen, Rob J.; Weiser, Sheri; Johnson, Mallory O.; Turan, Janet M.
Abstract: The role of HIV disclosure and its influence on engagement in HIV care after initial linkage to care is not well understood. We conducted 28 in-depth interviews with patients newly entering HIV care. Gaining access to social support was a key reason that many patients disclosed their HIV status. For some, HIV disclosure improved support networks related to engagement in care at the time of care entry, in the form of appointment reminders, emotional support, and confidence to disclose more widely. However, some participants cited anticipated stigma as a barrier to disclosure, as they feared rejection or further disclosure without their permission. Early access to social support and skill building related to stigma reduction and coping can be useful resources to help patients manage HIV, as they initiate care. In addition, incorporating support for smart disclosure decisions into interventions may improve access to social support, ultimately improving engagement in care.